2013
DOI: 10.1002/jctb.4146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyaniline‐graphene nanosheets modified cathode on the performance of sediment microbial fuel cell

Abstract: BACKGROUND The limitation on output power is a great challenge for the practical application of sediment microbial fuel cells (SMFC). One of the effective strategies to overcome this problem is to develop better‐performing cathodes. RESULTS Polyaniline (PANI)‐graphene nanosheets (GNS) modified cathodes were fabricated and applied as the cathodes of SMFCs to improve their electricity generation capacity. PANI‐GNS cathodes were fabricated through situ‐polymerization of aniline in a solution containing homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 25 publications
1
27
1
Order By: Relevance
“…The properties of modified cathode can be readily tuned by the mass ratio of aniline and GNS in the precursor solution and optimized performance was achieved at the ratio of 9:1. The addition of highly conductive GNS assisted PANI-GNS electrode to outperform the PANI electrode with the highest output voltage of 640 mV and maximum power density of 99 mW/m 2 , much higher than the blank MFC [76]. …”
Section: Graphene-polymer Nanocomposites As Orr Catalystsmentioning
confidence: 92%
See 1 more Smart Citation
“…The properties of modified cathode can be readily tuned by the mass ratio of aniline and GNS in the precursor solution and optimized performance was achieved at the ratio of 9:1. The addition of highly conductive GNS assisted PANI-GNS electrode to outperform the PANI electrode with the highest output voltage of 640 mV and maximum power density of 99 mW/m 2 , much higher than the blank MFC [76]. …”
Section: Graphene-polymer Nanocomposites As Orr Catalystsmentioning
confidence: 92%
“…Similar to other types of fuel cells, cathode is of vital importance for improving the electricity generation of MFCs [76]. Graphene-polymer conjugated nanocomposites were thoroughly investigated as cathode electrode for rapid power output of MFC, due to their remarkable electron transfer efficiency and fast oxygen reduction rate.…”
Section: Graphene-polymer Nanocomposites As Orr Catalystsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) results revealed the diminished internal resistance for the PANI/GNS cathodes compared to the PANI cathode, with the PANI/GNS ratio of 9:1 being the most conductive electrode. Moreover, The PANI/GNS 0.1 -MFC exhibited the maximal power density of 99 mW m −2 due to the outstanding electrical conductivity, 116 times that of the blank MFC (0.85 mW m −2 ) [55]. PANI has been also used as an attractive precursor for synthesis of nitrogen-doped carbon material.…”
Section: Metal Free Catalysts Cathode Catalystsmentioning
confidence: 99%
“…PANI is one of the most widely used conductive polymers, and exhibits electrocatalytic activity toward the ORR. It has been demonstrated that the MFCs with a PANI-coated cathode generated more electrical energy than those without the PANI coating [43,49]. When PANI was doped with a certain amount of GNS to form a PANI-GNS cathode, the power density was further improved compared with the non-graphene-doped cathode electrode.…”
Section: Polymer Coating With Graphene As a Dopantmentioning
confidence: 99%
“…When PANI was doped with a certain amount of GNS to form a PANI-GNS cathode, the power density was further improved compared with the non-graphene-doped cathode electrode. The mass ratio between aniline and graphene was optimized to be 9 : 1 in order to achieve the highest maximum power density (0.10 W m −2 ) for this type of cathode electrode [43].…”
Section: Polymer Coating With Graphene As a Dopantmentioning
confidence: 99%